From Likes to Profit: The Impact of Digital Marketing on the Economic Growth of the MSME Sector - Wulandari, Wulandari (Nomico, 2025)
This study explores the impact of digital marketing on the economic growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. With the increasing prevalence of digital platforms, MSMEs have begun to utilize social media, e-commerce, and online advertising to reach wider audiences, enhance brand visibility, and boost revenue. The research employs a quantitative approach using surveys distributed to MSME owners across various sectors, analyzing the relationship between digital marketing practices and business performance. The findings indicate a strong positive correlation between digital marketing intensity and business growth, particularly in terms of customer acquisition, revenue generation, and market expansion. However, the study also reveals challenges such as limited digital skills, infrastructure disparities, and algorithm changes that hinder optimal results. The research suggests that for MSMEs to fully capitalize on digital marketing, consistent effort, strategic planning, and digital literacy enhancement are essential. This study contributes to the understanding of digital marketing’s role in MSME development and offers recommendations for policy interventions and business strategies.